Old Bear - Hissey, Jane. (New York : Philomel Books, 1986)
A group of toy animals try various ways of rescuing Old Bear from the attic.
Book Links (A.L.A.).
Booklist.
Kirkus Review.
4.3
K-3
Keywords: Toys -- Fiction; Old Bear (Fictitious character) -- Fiction; Toys -- Fiction; Old Bear (Fictional character) -- Fiction; Toys -- Fiction